“Some fuzzy math”: Relational information on debt value adjustments by managers and the financial press - Kaumanns, Sebastian (Springer Nature, 2020)
This study provides comprehensive descriptive evidence on the occurrence, size, and reporting by managers and the ﬁnancial press of debt value adjustments due to a change in own credit risk (DVAs). The study is motivated by a public debate about DVAs in which critics describe them as ‘‘counterintuitive’’ and claim that managers disclose DVA information strategically to make ﬁrms ‘‘look good’’. Analyzing a sample of 405 ﬁrm-quarters of 19 US ﬁnancial ﬁrms that report DVAs between 2007 and 2014, I found that positive and negative DVAs appear similarly often and with similar magnitude. I further found that managers provide more information on large negative DVAs compared to positive DVAs. Managers also provide more DVA information when they have strategic incentives to do so. Examining newspaper articles on 202 ﬁrm-quarters, I found that the ﬁnancial press is more likely to cover large positive DVAs and DVAs about which managers provided more information. Analyzing the articles’ content, I found that the press is more likely to provide new DVA information if managers’ press releases contain little information. The ﬁndings are in line with popular claims of asymmetric DVA reporting by managers. They are further consistent with the ﬁnancial press acting as a counterweight to such asymmetric reporting.